Profesionalisme Guru dan Strategi Menghadapi Degradasi Moral di Era Globalisasi - Zachroh, Siti Apipah; Fahrun, Elva (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2024)
The rapid development of the times brings many changes, it also brings impacts on the world of Education, the development of times can not be fought rather should be made as friends, including in the world Education all who are involved in it are required to adapt more quickly. It is a challenge for teachers to continue to innovate in communicating information without separating knowledge from existing technological developments, by constantly upholding every change with the prescribed legal norms, so that as changes do not occur unwanted moral and ethical degradation, through ability as well as professionalism, a teacher is expected to be able to respond to the anxiety of moral degeneration in the students who are increasingly becoming. This research aims to provide innovation as well as motivation for a teacher to continue to increase knowledge as a reference in the face of educational challenges in the era of globalization. As for this research, using a library study method. The results of the study conclude that the collaboration of teachers and parents is important in tackling moral degradation. Regular meetings to discuss student development help create an integral moral understanding of the two main environments: home and school. Educating positive behavior in school through rules that support discipline, honesty, and accountability is also effective. Abstrak Pesatnya perkembangan zaman membawa pada banyak perubahan, hal ini juga membawa dampak pada dunia Pendidikan, perkembangan zaman memang tidak bisa dilawan justru seharusnya dijadikan sebagai kawan, termasuk di dalam dunia Pendidikan semua yang terlibat di dalamnya dituntut untuk lebih cepat beradaptasi. Hal ini menjadi sebuah tantangan bagi guru untuk terus berinovasi dalam menyampaikan informasi tanpa memisahkan antara pengetahuan dengan perkembangan teknologi yang ada, dengan terus membentengi tiap perubahan dengan norma hukum yang sudah ditentukan, sehingga seiring dengan adanya perubahan tidak terjadi degradasi moral dan etika yang tidak diinginkan, melalui kemampuan juga profesionalisme, seorang guru diharapkan mampu menjawab kegelisahan akan degradasi moral pada siswa yang kian hari semakin menjadi. Penelitian ini bertujuan untuk memberikan inovasi juga motivasi bagi seorang guru untuk terus memperbanyak pengetahuan juga referensi dalam menghadapi tantangan pendidikan di era globalisasi. Adapun dalam penelitian ini menggunakan metode kajian pustaka. Hasil penelitian menyimpulkan bahwa kolaborasi guru dan orang tua penting dalam mengatasi degradasi moral. Pertemuan rutin untuk mendiskusikan perkembangan siswa membantu menciptakan pemahaman moral yang utuh dari dua lingkungan utama: rumah dan sekolah. Pembiasaan perilaku positif di sekolah melalui aturan yang mendukung sikap disiplin, kejujuran, dan tanggung jawab juga efektif.